Geographical factor dominates spatial patterns of potential nitrate reduction rates in coastal wetland sediments in Fujian Province, China - Zhang, Ning; Dai, Zetao; Wang, Feifei; Yang, Shengchang; Cao, Wenzhi (Frontiers in Earth Science, 2024)
Nitrate (NO3 -) reduction is a key process governing the nitrogen (N) dynamics of coastal wetland sediments. Although the effects of environmental factors on the NO3 -reduction mechanism in coastal wetland sediments have been examined in various studies, the effects of spatial variation in potential NO3 -reduction processes in coastal wetland sediments and the factors driving geographical variation in these processes have not been widely examined. Here, we conducted research on surface sediment samples from four different vegetation types at six coastal wetland sites across two regions. We characterized potential rates of NO3 -reduction processes (including denitrification (DF), anammox (ANA), and dissimilatory nitrate reduction to ammonium (DNRA)) using a 15 N tracer method. Additionally, we assessed the abundances of functional genes, and microbial community structure using high-throughput sequencing, and metagenomic sequencing. In six wetland sites, the contribution ranges of DF, ANA, and DNRA to NO3 -reduction were 38.43-55.69%, 31.33-45.65%, and 5.26-17.11%, respectively, and potential NO3 -reduction was mainly driven by N removal via gaseous N (DF+ANA). Significant spatial differences were observed in the structure of bacterial and fungal microbial communities, suggesting that geographical distance has a major effect on microbial community structure. Environmental factors and Functional gene abundances were significantly related to potential NO3 -reduction processes, and physicochemical properties had a stronger effect on potential NO3 -reduction processes than gene abundances. Factors showing significant differences across regions were the main drivers of variation in potential NO3 -reduction processes. Overall, our study showed that sediment substrates and geographical environmental factors rather than the abundance of functional genes and vegetation types were the main indicators of potential NO3 - reduction activities in coastal wetlands.